Character Education for Environmental Awareness through the Adiwiyata Program - M. Khoirul Yasin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
The Adiwiyata program is implemented to realize responsible school members for environmental protectionand management efforts through good school governance to support sustainable development. The Adiwiyataprogram combines learning and action, thus it provides effective methods for changing behavior. AdiwiyataSchool is expected to be an agent of change for the community around the school. Schools must be a model increating a healthy and comfortable environment and become a model in realizing school citizens who areenvironmentally friendly and cultured. This study aims to analyze the implementation of the AdiwiyataProgram in the development of environmental awareness in the Adiwiyata Mandiri School, SMAN 1 Kajen,Pekalongan Regency. This research uses a qualitative approach with case study. The research subjects wereselected by purposive sampling technique, consisting of key informants and supporting informants. Datacollected through observation, interviews, and documentation. The data validity technique uses triangulationof techniques and sources. The results showed that the implementation of the Adiwiyata Program was carriedout in four aspects: (1) aspects of environmentally friendly school policies, (2) aspects of environment-basedschool curricula, (3) aspects of management of infrastructure that supports environmentally friendly schools,and (4) aspects of activity-based participatory and overall contribute positively in creating situations andconditions that support the development of environmental awareness.